Is Self-Determined Motivation a Useful Agent to Overcome Perceived Exercise Barriers in Patients With Type 2 Diabetes Mellitus? - Kang, Heon Jin; Wang, John Chee Keng; Burns, Stephen Francis; Leow, Melvin Khee-Shing (Frontiers in Psychology, 2021)
Background Devising a program to increase physical activity (PA)/exercise behavior in patients with type 2 diabetes mellitus (T2DM) can meet with limited effectiveness in real-world settings because of the variety of barriers to PA/exercise that individuals need to overcome. An alternative approach is to explore whether targeting motivation as a facilitator may be effective to increase PA/exercise. This study aimed to understand attitudes towards perceived barriers to PA/exercise by examining individual levels of motivation, grounded on self-determination theory, in patients with T2DM. Methods This study used an integrated approach combining qualitative and quantitative analysis. Sixteen patients with T2DM were grouped (n=8 for each group) into either a higher self-motivation (HSM) or lower self-motivation (LSM) group via the Relative Autonomy Index. Thematic and deductive analysis were used to identify attitudes based on ten preconceived barrier themes: apathy, dislike, no priority, lack of support, health problems, lack of knowledge, unfavorable environment, tiredness, lack of time, and financial constraints. Quantitative analysis was to assess statistical differences in the volume of PA/exercise across the two groups, and a mixed-methods analysis was employed to highlight unique cases. Results Patients in the HSM group expressed positive attitudes toward barriers to PA/exercise, while patients in the LSM group expressed a greater degree of hindrance. Although regular PA/exercise is necessary for T2DM management, patients with LSM considered PA/exercise a lesser priority displaying negative attitudes such as apathy and dislike. Conversely, patients with HSM placed greater emphasis on the benefits of PA/exercise regardless of apathy and dislike. Lack of time and health problems were commonly reported in both groups. The volume of PA/exercise corresponded to motivation levels, but there were some unique cases arose from active commuting habits and severe health problems. Conclusion These findings provide insights on how attitudes to perceived barriers to PA/exercise differ by levels of motivation. One insight was that examining motivation should be an essential consideration when designing practical strategies to overcome PA/exercise barriers in patients with T2DM. Lack of time and health problems exist regardless of motivation levels. Future research requires a tailored approach to managing barriers to PA/exercise in patients with T2DM.